The influence of lifestyle and financial literacy on financial management for student at fajar university (case studies in the management study program) - Sugeng, Rachmat; Sari, Dita Indah (Institute of Computer Science (IOCS), 2025)
This study aims to find out how lifestyle and financial literacy influence financial management for students at Fajar University in the management study program. This research is a descriptive quantitative study using a purposive sampling technique involving 80 respondents who were given questionnaires and then statistically analyzed using IBM SPSS 24 with the validity test approach, reliability test, normality test, multiple linear regression and hypothesis testing t and f and test the coefficient of determination. The results of this study show that lifestyle and financial literacy have a positive and significant effect both partially and simultaneously on student financial management at Fajar University by 22.7%.